Export-led growth v2.0 - Canuto, Otaviano; Haddad, Mona; Hanson, Gordon (World Bank, Washington, DC, 2012)
The United States (U.S.) recession could hurt the South, particularly in oil and apparel exports, and Latin America and the Caribbean. But South-South trade is partly picking up the slack. Middle-income countries are driving export diversification of low-income countries. Developing countries may be moving toward a new version of export-led growth.